Pengambilan Keputusan Perokok Tembakau Yang Beralih Ke Rokok Elektrik - Sakti Tri Atmojo, Wahyu, Dr. Nanik Prihartanti,M.Si., Psi (2017)
Smoking is a problem that can not be solved until today. Many effects and risks of smoking actually been published to the public, but peoples smoking habit still hard to break. Average cigarettes smoked per day Indonesian population aged ≥10 years was 12.3 pcs. There is an effective way to quit smoking, that is using Nicotine Replacement Therapy (NRT). Nicotine replacement therapy (NRT) is a method that use a tool to provide the nicotine which smoker need without a danger of tobacco burn. Electronic cigarettes (electronic cigarettes) or e-cigarette is one of the NRT that uses electricity from the batteries to deliver nicotine in vapor form and by WHO called as as Electronic Nicotine Delivery Systems (ENDS). The aim of this study is to know about tobacco smoker decision making process who switch to electronic cigarette. This study use qualitative research methods descriptive phenomenology. Subjects in this study is 10 people with the following criteria: (a) Minimum age 18 years, (b) using an electric cigarette at least 1 month, and (c) user of tobacco cigarettes previously. This study use interview method for data collection. Data were analyzed thematically. The results of this study showed that the decision-making tobacco smokers who switch to the electric cigarette is influenced by internal and external factors. Internal factors include the perception and knowledge about tobacco cigarettes. External factors include peoples around subjects.